Industrial training report / Muhammad Aslam Hasin - Hasin, Muhammad Aslam (2015)
As part of graduation requirements, all the undergraduates, the second year and third year students, who take Diploma of Electrical Engineering in UiTM Terengganu will undergo industrial training programme for duration of eight weeks. This industrial training is a course for undergraduates that gives them an opportunity to expose themselves in the real career world so as to they will learn how to relate theoretical learning before and real practical in working’s environment. Besides that, in future, they will be having good preparation and understanding for their field of profession. Through this exposure, students will have better understanding of engineering practice in general and sense of frequent and possible problems. This training is part of the learning process. So, the exposure that uplifts the knowledge and experience of a student needs to be properly documented in the form of a report. Through this report, the experience gain can be delivered to their peers. A properly prepared report can facilitate the presentation of the practical experience in an orderly, precise and interesting manner.